EFFECT OF FEED QUAliTY RESTRICTION FOLLOWED BY REAUMENTATION ON GROWTH, NUTRIENT UTILIZATION, BIOCHEMICAL CHANGES AND HAEMATOLOGICAL PROFILES OF INDIAN MAJOR CARP, ROHU (LABEO ROHITA. H.)
To investigate the effect of protein restriction with subsequent realimentation on nutrient utilization, haematological and biochemical changes of Indian major carp, Rohu l..abeo rohita H.), 150 acclimatized Rohu fingerlings (average 20.74 ± 0.13 g) divided into five experimental groups (30 fingerlings in each groups with three replications with 10 fingerlings in each) for experimental trial of 90 days using completely randomized design. Control group TcPR) was fed with feed having 30% crude protein@ 3% of body weight for 90 days trial period. Other experimental groups T1PR was alternatively 3 days fed with feed having 20% CP and 30% CP@ 3% of body weight, T2PR was alternatively 7 days fed with feed having 20% CP and 30% CP@ 3% of body weight, T3PR was alternatively 15 days fed with feed having 20% CP and 30% CP@ 3% of body weight and T4PR was alternatively 25 days fed with feed having 20% CP and 30% CP@ 3% of body weight during 90 days trial period with daily ration in two equal halves at morning and afternoon. It was noticed that retention of different nutrients was almost similar among all treatment groups indicated improvement of digestibility of nutrients might not be the mechanisms for recovery growth in carps. Increased percent feed intake of body weight (hyperphagia) (4.14 ± 0.30 or 4.94 ± 0.46 and 3.33 ± 0.29), improved specific growth rate (1.86 ± 0.09 or 2.26 ± 0.05 and 1.43 ± 0.01), absolute growth rate (1.57 ± 0.08 or 1.84 ± 0.18 and 1.36 ± 0.12), protein efficiency ratio (1.19 ± 0.11 or1.16 ± 0.12 and 1.05 ± 0.09) were the important mechanism showing better performance index 21.60 ± 1.09 or 23.80 ± 0.21 and 19.45 ± 0.37) through which the experimental groups which were protein restricted and re-alimented at 3 or 7 days alternatively during 90 days trial period could able to compensate the growth retardation and to catch up the final body weight of control (128.68 ± 11.53 g/f) but other experimental groups failed to compensate during 90 days trial period. Result of the present study indicated that deprived fish i.e., fish received alternate 3 or 7 days protein restriction andre-alimentation showed recovery growth had still lower values of Hb 10.21 ± 0.02, and 9.88 ± 0.04 g/dl), haematocrit value (30.62 ± 0.05 and 26.64 ± 0.11%), total erythrocytic count (3.40 ± 0.01 and 3.29 ± 0.01 X106 mm3 ), plasma glucose 126.93 ± 0.20 and 126.67 ± 0.05 mg/dl), total plasma lipid (1.04 ± 0.01 and 1.02 ± 0.01 g/dl and liver glycogen 290.10 ± 0.80 and 288.99 ± 0.95 mg/kg) in comparison to control (10.56 ± 0.08 g/dl, 31.68 ± 0.24%, 3.52 ± 0.03 X106 mm3 , 128.23 ± 0.25 mg/dl, 1.07 ± 0.01g/dl and 292.00 ± 0.23 mg/kg) at the end of 90 days trial but total plasma protein in deprived group was compensated with advancement of trial period. All 142 Parimal Sardar*, S. K. Prabhakar, S.C. Dutta and H. S. Minhas haematological and biochemical parameters studied were proportionately lowered in the experimental group got higher degree of deprivation. These findings suggested that with the increase of trial length complete compensation of haematological and biochemical profiles of rohu might be achieved. The results indicated that the implementation of alternative 1 days low and high protein diet feeding during aquaculture of carps could make economize the operation through minimizing the feed input cost. Key Words: protein restriction, growth, re-alimentation, nutrient utilization, haematological profiles, biochemical changes, Rohu Labeo rohita). , journal=Journal of Indian Fisheries Association, author=Sardar, Parimal and Prabhakar, S. K. and Dutta, S. C. and Minhas, H. S., year=2008, month=Dec.